(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Odisha has 62 distinct tribal groups, making it the largest collection of tribal people in a single state in the country. Each of these tribal groups has its own indigenous customs and continues to practice them even today. It is home to India’s ancient civilization and most of it is concentrated around the Eastern Ghat hill ranges in the region of Koraput, Sundargarh and Mayurbhanj. The antiquity of Orissa is endorsed by her ancient people who continue to inhabit their traditional dwelling places in remote areas in the deep forests and hilly interiors. Steeped in the mystery that surrounds their ancient ways, the Odishan tribals continue to be a source of deep interests of scholars from various disciplines.